TINJAUAN SISTEMATIS FAKTOR-FAKTOR YANG MEMPENGARUHI SERVICE QUALITY RUMAH SAKIT: PERSPEKTIF SERVQUAL, KEPUASAN PASIEN, DAN KINERJA ORGANISASI KESEHATAN - Fauzie Maulana; I Made Agus Satria Naradha; Hanifah Deka Insani; I Made Rai Wiana; Izza Ahmad Muharis; A. Rohendi (CV. Denasya Smart Publisher, 2026)
Hospital service quality has become a crucial aspect in an increasingly competitive global healthcare system. This systematic review aims to identify factors influencing hospital service quality based on the SERVQUAL model perspective, patient satisfaction, and healthcare organizational performance. The Systematic Literature Review method was employed by analyzing 15 high-quality studies from various electronic databases covering the period 2021-2025. Results indicate that all five SERVQUAL dimensions significantly affect service quality, with empathy as the strongest predictor, followed by assurance, responsiveness, reliability, and tangibility. A consistent positive relationship was found between service quality dimensions and patient satisfaction across various hospital settings, despite variations based on institutional type and demographic characteristics. Service quality and patient satisfaction contribute to organizational performance through complex mechanisms involving loyalty, trust, and long-term commitment. Internal organizational factors such as adaptive leadership, employee engagement, and organizational support mediate these relationships. These findings provide practical implications for hospital management in designing evidence-based service quality improvement strategies and serve as a reference for developing health policies that are more responsive to patient needs.